Management of pests of cowpea and salad cucumber in polyhouse - Thamilarasi N (Department of Agricultural Entomology, College of Agriculture, 2016)
A study on “Management of pests of cowpea and salad cucumber in polyhouse” was undertaken in polyhouses of Thiruvananthapuram district and College of Agriculture, Vellayani during January 2015 to May 2016. The main objectives were to document the pests and natural enemies on cowpea and salad cucumber in polyhouses and to evaluate the efficacy of new generation insecticides against the major pests. A purposive survey was conducted in 20 polyhouses in Thiruvananthapuram district to document the pests and natural enemies. Sucking pests viz., pea aphid, Aphis craccivora (Koch), mealy bug, Ferrisia virgata (Cockerell), pod bug, Riptortus pedestris (Fabricius), fulgorid bug, Eurybrachys tomentosa (Fabricius), thrips, Ayyaria chaetophora (Karny), spotted red mite, Tetranychus truncatus (Ehara) and leaf feeders viz., pod borer, Lampides boeticus (Linnaeus), tobacco caterpillar, Spodoptera litura (Fabricius), leaf beetle Pagria flavopustulata (Baly), American serpentine leaf miner, Liriomyza trifolii (Burgess) are the pests associated with cowpea. New pests viz., tortrycid larvae, leaf miner and girdle beetle, Oberiopsis brevis (Gahan) were reported from cowpea under polyhouse. Sucking pests viz., green peach aphid, Myzus persicae (Sulzer), mealy bug, Ferrisia virgata (Cockerell), thrips, Astrothrips tumiceps (Karny), Thrips hawaiiensis (Morgan), Frankliniella schultzei (Trybom) spotted red mite, Tetranychus sp, and leaf feeders viz., pumpkin caterpillar, Diaphania indica (Saunders), American serpentine leaf miner, Liriomyza trifolii (Burgess) are associated with salad cucumber under polyhouse conditions. The natural enemies observed were coccinellids, syrphids and spiders viz., Oxyopes javanus (Thorell), Oxyopes sunandae (Tikader) and Argiope pulchella (Thorell) from both cowpea and salad cucumber. The data on preliminary survey revealed that both sucking and leaf feeder pests caused significant damage to cowpea and salad cucumber inside polyhouse.Experiments were carried out in CRD to evaluate the efficacy of new generation insecticides viz. acetamiprid 0.10 g L -1 , imidacloprid 0.20 mL L -1 , thiamethoxam 0.30 g L -1 , thiacloprid 0.25 mL L -1 , dimethoate 1.50 mL L -1 against sucking insects viz., A. craccivora, M. persicae and R. pedestris and acaricides viz., spiromesifen 0.80 mL L -1 , fenpyroximate 0.60 mL L -1 , dimethoate 1.50 mL L -1 against Tetranychus sp. Spinosad 0.30 mL L -1 , chlorantraniliprole 0.30 mL L -1 , flubendiamide 0.10 mL L -1 , indoxacarb 1.00 mL L -1 , quinalphos 3.00 mL L -1 were tested against leaf feeders viz., L. trifolii and D. indica. Evaluating the efficacy of new generation insecticides, thiamethoxam 0.30 g L -1 and imidacloprid 0.20 mL L -1 were found to be effective against sucking pests which reduced the mean population of A. craccivora to 7.33 and 12.67 aphids plant -1 respectively and M. persicae to 4.67 and 11.67 aphids plant -1 respectively after 15 days of treatment. However, thiamethoxam 0.30 g L -1 and imidacloprid 0.20 mL L -1 were found to be equally effective in managing R. pedestris which reduced the population to 0.20 bugs plant -1 . Spiromesifen was recorded to be the best by reducing the population to 10.50 and 16.25 mite plant -1 in cowpea and salad cucumber respectively. Chlorantraniliprole 0.30 mL L -1 and spinosad 0.30 mL L -1 reduced the population of leaf miner to 0.60 and 0.40 larvae plant -1 in cowpea respectively and 0.20 and 0.60 larvae plant -1 in salad cucumber respectively and no larvae of D. indica were recorded in chlorantraniliprole 0.30 mL L -1 and flubendiamide 0.10 mL L -1 treated salad cucumber 15 days after spraying. The dissipation (persistence/ degradation of residues) study showed that the promising insecticide thiamethoxam 0.30 mL L -1 persisted upto 7 and 5 days in cowpea and salad cucumber respectively and imidacloprid 0.20 mL L -1 persisted upto one day in both cowpea and salad cucumber and spiromesifen 0.80 mL L -1 persisted upto 7 and 5 days in cowpea and salad cucumber respectively. Chlorantraniliprole 0.30 mL L -1 and spinosad 0.30 mL L -1 persisted upto 5 and 7 days in cowpea and 3 days each in salad cucumber respectively.From the present study it is concluded that both sucking pests and leaf feeders are causing significant damage in cowpea and salad cucumber under polyhouse conditions. Application of thiamethoxam 0.30 g L -1 and imidacloprid 0.20 mL L -1 effectively manage the sucking pests viz., A. craccivora, M. persicae and R. pedestris. Spiromesifen 0.80 mL L -1 was found to be the best to manage the Tetranychus sp. Chlorantraniliprole 0.30 mL L -1 and spinosad 0.30 mL L -1 were found to be effective in managing leaf feeders in both cowpea and salad cucumber. A harvest interval of 5 to 7 days should be given to ensure the safety of the produce from the polyhouse to the end users.